UNA APROXIMACIÓN CONEXIONISTA A LOS PROCESOS MENTALES ENTREVlSTA CON JAMES L. MCCLELLAND. - Pascual, Belén; McClellan, James L. (Anuario Filosófico, 2005)
In this interview, James L. McClelland responds to questions regarding connectionist models of cognition, a theory inspired by information processing in the brain. McClelland explains the distinction between symbolic and non-symbolic processing for a better understanding of mental processes. He argues that connectionist models can perform the computations which we know the brain can perform. In addition, he responds to several general questions on the perspectives of computational models of cognition.